Beneath politicization: the unacknowledged constitutional crisis in the Dagbon succession conflict in Ghana. Issue 2 (3rd May 2016) - Bolaji, M. H. A.
ABSTRACT: The Dagbon succession conflict has been intermittent since the colonial era. What appears to be the most trumpeted thesis in the scholarly works that the conflict has attracted is the over-politicization of the conflict. While the over-politicization of the conflict is indisputable, this study uncovers the constitutional crisis, which is beneath and motivates the over-politicization of the conflict. Through a critical content analysis of archival and historical documents (commission reports, letters, petitions, minutes, and court rulings, among others), and through secondary data from books, journal articles, and newspapers (both print and electronic), the paper identifies and explores three principal sources of the constitutional crisis, namely, the inadequacy of the 1930 Dagomba Succession Constitution, the lack of legitimacy for the 1948 Amended Dagomba Succession Constitution, and the state's interventions that have deepened the constitutional crisis. Having explained how legal centralism and legal pluralism have been implicated in the conflict, the paper concludes with a dispassionate call for a transformation of the conflict that will acknowledge the constitutional character of the conflict and the need to convene a constitutional conference in which the two royal gates would harmonize their emic perspectives on their succession customs and rules.